Analysis of Cryptocurrency Investment Determinants - Gigih Ganang Asyraf Rif’an (Universitas Muhammadiyah Yogyakarta, 2022)
Various financial products have emerged in the era of the digital economy, including cryptocurrencies. In Indonesia, the Commodity Futures Trading Regulatory Agency (CoFTRA) regulates the use of cryptocurrencies. Cryptocurrencies are designated as investment assets that can be included as commodities in trading on futures exchanges but are prohibited from being used as a means of payment. Crypto investors in Indonesia alone in 2021 have reached 6.5 million people with a transaction value of Rp 370 trillion as of May 2021. This number continues to increase from the previous year, making crypto investors bigger than stocks or mutual funds. This study then analyzes the factors influencing the Indonesian people's interest in investing in cryptocurrencies. Data collection techniques were collected through questionnaires distributed online to 97 respondents, while data processing used multiple regression analysis. The findings of this study indicate that yield and flexibility have a positive and significant effect on interest in investing in cryptocurrencies. Meanwhile, the prohibition of cryptocurrencies has a negative impact on interest in investing in cryptocurrencies.